ANALISIS PENGARUH RASIO LEVERAGE, AKTIVITAS DAN PROFITABILITAS TERHADAP NILAI PERUSAHAAN (Studi Empiris Pada Perusahaan Manufaktur Sektor Industri Dasar Dan Kimia yang Terdaftar di BEI Dalam Kurun Waktu 2018-2020) - Kay, Sahyuni; Pamungkas, Leo Dadyo; Nurcahyo, Narwanto (Program Studi Manajemen, 2022)
This study uses a quantitative descriptive approach with a purposive sampling technique for collecting data. This research was conducted using the documentation method using annual financial statement data for companies listed on the Indonesia Stock Exchange in 2018-2020. The results of this study indicate that, (1) leverage (DER) has a negative effect on firm value (PER), this is indicated by a significant value of 0.007 which means it is smaller than = 0.05 with a coefficient value of -3.514. (2) activity (TATO) has no effect on firm value (PER), this is indicated by a significant value of 0.147 which means it is greater than = 0.05 with a coefficient value of 0.508. (3) profitability has a positive effect on firm value (PER), this is indicated by a significant value of 0.043 which is smaller than = 0.05 with a coefficient of 2.908.